HUBUNGAN PERSEPSI RASA AMAN DENGAN SIKAP PEKERJA TERHADAP PENERAPAN MANAJEMEN PENANGGULANGAN KEBAKARAN DI PT.X - Windi Dwi Hapsari; Ida Wahyuni; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
The textile industries have a high fire risk because of the processes was involving flammable materials in large quantities.Therefore necessary precautions to minimize the risk of fire in the workplace is to implement fire prevention management. Perception of feeling safe is the process of assessment and understanding of the environment that produces a feeling of safe and has a role in determining the formation of attitude .The purpose of this research was to analyze the correlation between perception of feeling safe with workers attitude toward implementation of fire management in PT.X. The method used were quantitative with explanatory research and cross sectional approach. The total of population was 144 workers with 58 respondents of total sample. Chi Square test was used to analyze the data (significancy 0,05). The result of the research were 53,4% respondents have perception of the feeling safe is low and 51,7% respondents have the attitude that is less good. The result of Chi Square test showed that there was a correlation between perception of feeling safe with workers attitude toward implementation of fire management with p-value 0,001 (α < 0,05). The company needs to provide fire-fighting facilities include hydrants and smoke detectors in companies area and establish programs could that support the safety and security from the risk of fire.